The Influence of Spatial and Feature Probability Cuing in Visual Search. (April 2013) - Schwark, Jeremy; Dolgov, Igor
Certain aspects of a visual search task, such as the location where a target often appears, are learned over time and can serve as a source of attentional guidance. An example of this implicit learning, spatial probability cuing speeds detection of targets that appear in probable locations. The current study investigated target feature probability learning and its relation to implicit spatial probability learning. Results reveal that individuals are sensitive to small changes in the spatial probability of targets, even incidentally learning moderate probabilities. However, feature-based probability differences impacted visual search times much less. Implications for these findings are discussed.